Time Lag Analysis of Atmospheric CO2 and Proxy-Based Climate Stacks on Global–Hemispheric Scales in the Last Deglaciation - Zhi Liu; Xingxing Liu (Quaternary)
Based on 88 well-dated and high-resolution paleoclimate records, global and hemispheric stacks of the last deglacial climate were synthesized by utilizing the normalized average method. A sequential relationship between the West Antarctic Ice Sheet Divide ice core CO2 concentration and the composited proxy-based global–hemispheric climate stacks was detected using the Wilcoxon rank-sum test and wavelet analysis. The results indicate that the climate stack of the Northern Hemisphere started to increase slowly before 22 kabp, possibly due to the enhancement of summer insolation at high northern latitudes, the onset of warming in the Southern Hemisphere occurred around 19 kabp, and the atmospheric CO2 concentration began to raise around 18.1 kabp. This suggests that the change in northern high-latitude summer insolation was the initial trigger of the last deglaciation, and atmospheric CO2 concentration was an internal feedback associated with global ocean circulation in the Earth’s system. Both the Wilcoxon rank-sum test and wavelet analysis showed that during the BØlling–AllerØd and the Younger Dryas periods there was no obvious asynchrony between the global climate and atmospheric CO2 concentration, which perhaps implies a fast feedback–response mechanism. The seesawing changes in interhemispheric climate and the abrupt variations in the atmospheric CO2 concentration could be explained by the influences of Atlantic meridional overturning circulation strength during the BØlling–AllerØd and the Younger Dryas periods. This reveals that Atlantic meridional overturning circulation played an important role in the course of the last deglaciation.